ANALISIS KELAYAKAN PENGEMBANGAN USAHA KERIPIK GADUNG BERKAH DI KABUPATEN PURWOREJO - , (Jurnal Akuntansi Pajak dan Manajemen (TAJAM), 2023)
This study aims to describe the business feasibility study at BERKAH in terms of non-financial aspects, namely market and marketing aspects, environmental aspects, technical aspects, human resources and social aspects. The research method used in the BERKAH business related to this business feasibility study is applied research and evaluation. Analysis of market and marketing aspects using Segmenting, Targeting, Positioning (STP), and Marketing Mix (Marketing Mix). Analysis of environmental aspects carried out is to analyze the evaluation of environmental impacts. Analysis of technical aspects is done by determining the raw materials. Analysis of aspects of human and social resources is to analyze the organizational structure and provide benefits to the surrounding community